Reducing Results Delivery Time for Couples Undergoing Carrier Screening: A "Tandem-Reflex" Strategy [24G]. (May 2020) - Arjunan, Aishwarya; Kaseniit, Kristjan Eerik; Wootton, Jeff; Taber, Katherine Johansen
Abstract : INTRODUCTION: Obtaining carrier screening results in a timely manner is important to support reproductive decision-making. Reproductive partners are typically tested in a sequential manner: the female is tested first and if a carrier, her partner is tested. This imposes workflow challenges due to the need for a subsequent visit to draw the partner's sample, reducing the likelihood of the partner getting screened and hampering detection of at-risk couples. We implemented a "tandem reflex" strategy wherein both partners submit samples in tandem but are tested sequentially, with the second partner's sample tested only if the first partner was found to be a carrier. METHODS: The time to delivery of a combined report was measured before and after implementation of the "tandem reflex" strategy. Comparison to a simultaneous strategy, ie, both partners samples tested as soon as they are received, is also reported. RESULTS: Before implementing the "tandem reflex" strategy, the average time for a sequentially tested couple to receive a report was 35 days (95th percentile 76 days, N=16, 785 couples). After implementation, the average time was reduced to 15 days (95th percentile 25 days, N=1, 132 couples). Among 13, 161 couples tested simultaneously, 42% of females were negative for all tested conditions; in this scenario, the tandem reflex strategy would have reduced unnecessary testing because it would not have triggered testing of the male partner. CONCLUSION: The "tandem reflex" strategy time to receipt of a combined report by half, allowing for more timely reproductive and pregnancy management.